2011
DOI: 10.1007/s00417-011-1673-1
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor: the driving force in initiation of RPE cell proliferation

Abstract: Background To analyze whether epidermal growth factor (EGF) exerts regulatory effects on proliferation and differentiation in ARPE19 cells after different incubation periods (24 vs. 48 h) for obtaining ideal conditions for feasible rejuvenation and autologous transplantation of retinal pigment epithelial cells (RPE cells). Methods To evaluate gene expression patterns of RPE-specific differentiation and proliferation markers as well as transcriptional and translational changes of beta-catenin (ß-catenin)-sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…Therefore, EGF is considered a major factor in the development of PVR [8,11]. In this study, we found that EGF-dependent proliferation and migration in RPE cell were inhibited by 1.0 μM AF (Fig 5).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Therefore, EGF is considered a major factor in the development of PVR [8,11]. In this study, we found that EGF-dependent proliferation and migration in RPE cell were inhibited by 1.0 μM AF (Fig 5).…”
Section: Discussionsupporting
confidence: 52%
“…Several studies have shown that EGF induces the EGFR/MAPK signal transduction pathway and contributes to the survival, proliferation and migration of RPE cells [68]. Therefore, EGF is considered a major factor in the development of PVR [8,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies found that EGF is capable to initiate proliferation and epithelial-mesenchymal transition of RPE cells through Wnt pathway. [27][28] Our MTS data indicated that 6hr treatment of 10ng/ml EGF could promote ARPE-19 cell proliferation. Xu and Yu [12] reported that EGFR activation played an important role in ARPE-19 cell wound-closure.…”
Section: Discussionmentioning
confidence: 76%
“…EGF plays an important role in cell proliferation, migration and locomotion (11e13). It induces the proliferation of different types of cells, for instance, the growth of keratinocytes of the skin and oropharynx, and retinal pigment epithelial cells, without inducing differentiation (11,12,14,15). EGF and its related peptides have been implicated in the promotion of cell proliferation in wound healing such as in re-epithelialization (12).…”
mentioning
confidence: 99%